2010
DOI: 10.1007/s10750-010-0309-5
|View full text |Cite
|
Sign up to set email alerts
|

Feeding preferences of the sandhopper Orchestoidea tuberculata: the importance of algal traits

Abstract: Factors such as nutritional quality and the secondary metabolite content of food resources have been shown to influence the feeding behavior of herbivores in many marine habitats. For intertidal macroalgae consumers on sandy beaches, the influence of these factors on feeding behavior and the consequences on their performance is poorly understood. In this study, we evaluated the relationships of nutritional quality, chemical defenses (phlorotannins), and the structure of three macroalgal species that form the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 96 publications
3
37
0
6
Order By: Relevance
“…The selective utilization among various basal food resources can be attributed to nutritional quality and the potential availability of different food sources (Boettcher & Targett 1993, Jormalainen et al 2005, Rodil et al 2008, Duarte et al 2010, Seymour et al 2013. In the present study, U. lactuca had lower C/N ratios compared with S. muticum or G. lemaneiformis, indicating the relatively high food availability of U. lactuca for A. japonicus, as organic nitrogen is more readily utilized than organic carbon (Danovaro et al 2001).…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…The selective utilization among various basal food resources can be attributed to nutritional quality and the potential availability of different food sources (Boettcher & Targett 1993, Jormalainen et al 2005, Rodil et al 2008, Duarte et al 2010, Seymour et al 2013. In the present study, U. lactuca had lower C/N ratios compared with S. muticum or G. lemaneiformis, indicating the relatively high food availability of U. lactuca for A. japonicus, as organic nitrogen is more readily utilized than organic carbon (Danovaro et al 2001).…”
mentioning
confidence: 51%
“…Different basal food resources, e.g. brown, red and green algae, generally have distinctive biochemical compositions and consequently different nutritional values and food quality, which could po tentially influence the feeding selectivity of consumers (Danovaro et al 2001, Adin & Riera 2003, Jormalainen et al 2005, Rodil et al 2008, Duarte et al 2010. Although the biology of A. japonicus has been studied for several decades, research efforts on the feeding habits and food preferences are relatively scarce to date (Gao et al 2011, Sun et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Adin and Riera, 2003;Crawley and Hyndes, 2007;Duarte et al, 2010;Poore and Gallagher, 2012), however, Rossi et al (2010) described an opportunistic behaviour for amphipods that relied on seagrasses (Sargassum muticum) when this resource was deposited in large quantities on the shore, and Porri et al (2011) found an ephemeral relationship between amphipods and specific wrack subsidies in South Africa. Herein, we also describe an opportunistic feeding behaviour, mainly of the consumers at Cabedelo beach, which might utilise the various sources indiscriminately as a result of the higher availability of wrack deposited on the shore.…”
Section: Discussionmentioning
confidence: 99%
“…Colombini et al, 2000;Duong and Fairweather, 2010;MacMillan and Quijón, 2012;Olabarria et al, 2007). The dietary wrack preferences of particular taxa (mainly amphipods) were also extensively studied, and while some studies showed similarly strong preferences for the brown algae (Adin and Riera, 2003;Crawley and Hyndes, 2007;Duarte et al, 2010;Olabarria et al, 2009), others showed that they are indiscriminate feeders (McLeod et al, 2013) and even not related with specific wrack species (Colombini et al, 2009;Porri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As características morfodinâmicas das praias onde foram realizados estudos de distribuição e ciclo de vida dessa espécie são do tipo dissipativo, de declive suave e granulometria fina com elevado aporte de algas arribadas. Talorchestia tucurauna apresenta um comportamento semelhante às demais espécies presentes em regiões temperadas e subtropicais como Talitrus saltador (Montagu, 1808), Bollorchestia quoyana (Milne-Edwards, 1840) e Orchestoidea tuberculata Nicolet, 1849 (Mardsen, 1991;Scapini et al, 1992;Duarte et al, 2010) que utilizam as algas arribadas como abrigo e alimento. Geralmente, as espécies associadas ao detrito vegetal estão localizadas na região superior do entremarés e no supralitoral, formando densas agregações embaixo das manchas de algas.…”
Section: Introductionunclassified